Guayaquil University constructs Experimental Station in warm tropical Agroplasticultura - Salcedo Rosales, Galo Alberto (Revista Universidad de Guayaquil, 2010)
The INEC said that eight out of 10 Ecuadorians living in poverty and two of them in extreme situa- tion. The small farms with low productivity, achieving only subsistence lifestyles. To exploit marginal lands, the University of Guayaquil and Almeria - Spain will work together to investigate Agroplasti- cultura in: efficient irrigation systems, high-nutrition cleaner production.The cultures for investigations are vegetables grown in protected conditions. The main components of the station are: greenhouses of various technologies, each with 40 m wide and 60 m long, with a northwesterly direction. The cover is plastic tricárpico, covered by a raft regulatory polyethylene geomembrane to ensure the provision of permanent water, irrigation station computer automated head irrigation and nutrient solution tanks. Head pipes are derived fertilizer-laden water. Gauges also has control of the efficiency of fertigation. Drainage system of rain water, road network, elec- tricity, infrastructure and training for transfer, soil laboratory, microbiology, biological control and organic fertilizer biofactories, post-harvest room, cold room for storage of harvested product.
Keywords: tricárpico; geomembrane; greenhouse; vegetables; computers; automated fertigation biofactories